2008
DOI: 10.1016/j.ejheart.2008.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Totally epicardial cardiac resynchronization therapy system implantation in patients with heart failure undergoing CABG

Abstract: Background: Systolic dyssynchrony is present in a considerable number of patients with heart failure (HF) undergoing coronary artery bypass grafting (CABG). Surgical revascularization offers an optimal setting for totally epicardial cardiac resynchronization therapy (CRT) system implantation. Aim: To assess the efficacy of totally epicardial CRT implantation during CABG, in patients with HF. Methods: Twenty three patients with HF and dyssynchrony underwent totally epicardial CRT system implantation during CABG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Overall Jehn et al 50 Radke et al 24 Alahdab et al 18 Alahdab et al 18 Rostagno et al 13 Rostagno et al 45 Ingle et al 26 Jehn et al 36 Ingle et al 26 Deuschle et al 52 Rostagno et al 46 Bagur et al 48 Zugck et al 21 Pepera et al 32 Goode et al 18 Deuschle et al 52 Faggiano et al 47 Leszek et al 35 Rostagno et al 13 Goode et al 7 Zugck et al 21 Ingle et al 26 Ingle et al 26 Rostagno et al 45 Tay et al 49 Jankowska et al 29 Bagur et al 48 Ates et al 30 Rostagno et al 46 Gary et al 25 Jehn et al 36 Karavidaset al 28 Souza et al 53 Jehn et al 50 Bosnak Güçlü et al 27 Alahdab et al 18 Forman et al 20 Zaidi et al Goscinska-Bis et al 37 Alahdab et al 18 Forman et al 20 Keast et al 31 Vrtovec et al 51 Rostagno et al 45 Souza et al 53 Tay et al 49 Jaski et al 34 Zugck et al …”
Section: Discussionmentioning
confidence: 99%
“…Overall Jehn et al 50 Radke et al 24 Alahdab et al 18 Alahdab et al 18 Rostagno et al 13 Rostagno et al 45 Ingle et al 26 Jehn et al 36 Ingle et al 26 Deuschle et al 52 Rostagno et al 46 Bagur et al 48 Zugck et al 21 Pepera et al 32 Goode et al 18 Deuschle et al 52 Faggiano et al 47 Leszek et al 35 Rostagno et al 13 Goode et al 7 Zugck et al 21 Ingle et al 26 Ingle et al 26 Rostagno et al 45 Tay et al 49 Jankowska et al 29 Bagur et al 48 Ates et al 30 Rostagno et al 46 Gary et al 25 Jehn et al 36 Karavidaset al 28 Souza et al 53 Jehn et al 50 Bosnak Güçlü et al 27 Alahdab et al 18 Forman et al 20 Zaidi et al Goscinska-Bis et al 37 Alahdab et al 18 Forman et al 20 Keast et al 31 Vrtovec et al 51 Rostagno et al 45 Souza et al 53 Tay et al 49 Jaski et al 34 Zugck et al …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a limited number of other studies have shown a beneficial effect of CRT and epicardial leads placed in association to cardiac surgery. In a small study on CRT with epicardial leads during CABG in patients with HF [12], a better estimated QoL was seen in patients with active CRT. Similarly, CRT improved QoL and LV systolic function after CABG in HF patients with ventricular dyssynchrony [13].…”
Section: Discussionmentioning
confidence: 99%
“…We did not detect any negative influence on QoL from CRT. Other authors have reported positive findings [12,13] and CRT may have a role in the treatment in selected patients with HF and ventricular dyssynchrony undergoing CABG and/or AVR surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such patients could have a CRT device implanted at the time of CABG surgery using epicardial pacing leads. A previous pilot study of the combined technique in 23 patients showed encouraging results 22…”
Section: Coronary Artery Bypass Grafting With Cardiac Resynchronimentioning
confidence: 90%